2012
DOI: 10.1590/s0074-02762012000100020
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of enteroinvasive Escherichia coli and Shigella flexneri by dendritic cells: distinct dendritic cell activation states

Abstract: The innate and adaptive immune responses of dendritic cells (DCs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
(22 reference statements)
0
9
0
3
Order By: Relevance
“…To this end, use has been made of experimental models that mimick the intestinal microenvironment of the host, such as cultures of intestinal epithelial cells, macrophages and dendritic cells 411, 415, 416. Our results showed that the initial ability to invade the intestinal cell is similar between EIEC and Shigella , but that the expression of virulence genes ( ipaABCD , icsA , icsB , virF , virB ), capacity to escape from the phagosome, intracellular proliferation and dissemination of EIEC, as well as the ability to cause cell damage during the infection, are much lower than with S. flexneri 411 .…”
Section: Enteroinvasive E Colimentioning
confidence: 99%
“…To this end, use has been made of experimental models that mimick the intestinal microenvironment of the host, such as cultures of intestinal epithelial cells, macrophages and dendritic cells 411, 415, 416. Our results showed that the initial ability to invade the intestinal cell is similar between EIEC and Shigella , but that the expression of virulence genes ( ipaABCD , icsA , icsB , virF , virB ), capacity to escape from the phagosome, intracellular proliferation and dissemination of EIEC, as well as the ability to cause cell damage during the infection, are much lower than with S. flexneri 411 .…”
Section: Enteroinvasive E Colimentioning
confidence: 99%
“…The illness caused by Shigella or EIEC is characterized by the destruction of the colonic epithelium caused by the inflammatory response induced upon invasion of the mucosa by bacteria ( Parsot, 2005 ). It is well established that the disease induced by EIEC is generally less severe than Shigella does ( DuPont et al , 1989 ; Moreno et al , 2009 ; Bando et al , 2010 ; Moreno et al , 2012 ). Recombination techniques and the sequencing of the invasion plasmid and chromosomal genes associated with virulence, gave insight of the precise mechanism of infection by Shigella .…”
Section: Pathogenesis Processmentioning
confidence: 99%
“…EIEC produce less severe disease than S. flexneri ( Moreno et al , 2009 ; Bando et al , 2010 ; Moreno et al , 2012 ). An inoculum of 10 6 EIEC cells is sufficient for infection, whereas as low as 10 2 Shigella cells can cause successful infection ( DuPont et al , 1971 ).…”
Section: Difference In Pathogenecity and Virulence Genes Expressionmentioning
confidence: 99%
“…Reduction of endogenous MUC17 in undifferentiated Caco-2 cells is associated with enhanced bacterial invasion in response to exposure to EIEC infection (765). Moreno et al (766) compared the innate and adaptive immune responses to EIEC and S. flexneri infection. EIEC triggered DC activation to produce IL-10, IL-12, and TNF-␣, whereas S. flexneri induced only the production of TNF-␣.…”
Section: Host Cellular Defense Responsesmentioning
confidence: 99%